2019
DOI: 10.1177/0149206319833445
|View full text |Cite
|
Sign up to set email alerts
|

Mind Your Language: The Effects of Linguistic Ostracism on Interpersonal Work Behaviors

Abstract: Business and demographic trends are conflating to bring language issues at work to the forefront. Although language has an inherent capacity for creating interpersonal bonds, it can also serve as a means of exclusion. The construct of linguistic ostracism encapsulates this phenomenon. Drawing on ethnolinguistic identity theory, we identify how linguistic ostracism influences two interpersonal work behaviors: interpersonal citizenship and interpersonal deviance. We conduct a set of studies that uses multisource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 96 publications
2
31
0
Order By: Relevance
“…The motives of linguistic ostracism are primarily to (1) make others feel rejected or uncomfortable (punitive), (2) bridge communication gaps caused by language deficiency and (3) a lack of awareness of the negative impact of using an unfamiliar language in the presence of others (Dotan-Eliaz et al , 2009). Language is entwined into the cultural fabric of the society, a medium by which workers communicate and share knowledge (Fiset and Bhave, 2019; Hitlan et al , 2016). Therefore, the inability to effectively communicate with others can increase a sense of in-group and out-group relationships (Hitlan et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The motives of linguistic ostracism are primarily to (1) make others feel rejected or uncomfortable (punitive), (2) bridge communication gaps caused by language deficiency and (3) a lack of awareness of the negative impact of using an unfamiliar language in the presence of others (Dotan-Eliaz et al , 2009). Language is entwined into the cultural fabric of the society, a medium by which workers communicate and share knowledge (Fiset and Bhave, 2019; Hitlan et al , 2016). Therefore, the inability to effectively communicate with others can increase a sense of in-group and out-group relationships (Hitlan et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interpersonal citizenship behaviors and interpersonal deviant behaviors reflect positive and negative orientations, respectively (Kabat-Farr & Cortina, 2017). Specifically, interpersonal citizenship behaviors indicate the depth of feeling for others in an organization (Brosi et al, 2016) and are regarded as positive (Luthans & Youssef, 2007;Podsakoff et al, 2009), while interpersonal deviant behaviors encompass actions that are detrimental to organizational functioning (Fiset & Bhave, 2021). These behaviors have been well established in the literature and are consistently related to affective processes (Brosi et al, 2016;Lee & Allen, 2002).…”
Section: Interpersonal Behaviors As Outcomesmentioning
confidence: 99%
“…In this context, a recent meta-analysis (i.e. Howard et al, 2020) has demonstrated that ostracism can trigger a gamut of negative outcomes, including, but not limited to, hampered performance (task-related performance, citizenship behaviors, counterproductive behaviors) (De Clercq et al, 2019;Fiset and Bhave, 2021;Jahanzeb et al, 2020;O'Reilly et al, 2015), reduced well-being, negative organizational perceptions (i.e. organizational injustice, reduced commitment, disengagement, dissatisfaction) (Boon and Brown, 2020;Miner et al, 2019) and employees leaving the organization (Vui-Yee and Yen-Hwa, 2019; Zhang et al, 2019;Zheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%